2019
DOI: 10.1016/j.prosdent.2019.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of high-speed sintering on translucency, phase content, grain sizes, and flexural strength of 3Y-TZP and 4Y-TZP zirconia materials

Abstract: STATEMENT OF PROBLEM The lengthy sintering time of zirconia is costly and limits applications. The consequences of shortening the sintering time are mainly unknown. PURPOSE The purpose of this in vitro study was to test and compare 2 high-speed sintering protocols and 1 conventional sintering protocol on the translucency, phase content, grain sizes, and flexural strength of 3 zirconia materials. MATERIAL AND METHODS In total, 450 specimens of 3 zirconia materials-two were 3 mol% yttria-stabilized tetragonal zi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
85
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 26 publications
(34 reference statements)
4
85
1
6
Order By: Relevance
“…Theoretically, the larger grains achieved with Prettau Anterior and Zpex Smile with the high‐speed sintering protocol should have increased their translucency due to the reduction in grain boundaries . A previous study also reported decreased translucency when a 5 mol% yttria‐containing zirconia was sintered with a high‐speed protocol . No explanation was given for the observation in the previous study.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Theoretically, the larger grains achieved with Prettau Anterior and Zpex Smile with the high‐speed sintering protocol should have increased their translucency due to the reduction in grain boundaries . A previous study also reported decreased translucency when a 5 mol% yttria‐containing zirconia was sintered with a high‐speed protocol . No explanation was given for the observation in the previous study.…”
Section: Discussionsupporting
confidence: 91%
“…Prettau Anterior and Zpex Smile experienced a 30% and 40% reduction in flexural strength, respectively, following high‐speed sintering. A previous study of 5 mol% yttria‐containing zirconia reported no effect on strength with a high‐speed sintering program . This result is consistent with the strength achieved with Katana STML Block with the high‐speed sintering protocols, but not the other zirconia materials tested in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations